(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Raising pulverized coal injection (PCI) will decrease coke rate, but increase the residence time of coke and abrasion in the blast furnace (BF). Thus, insufficient coke strength will generate more coke fines in the lower BF and result in lower permeability and production of hot metal (HM). For understanding the behavior of coke at various HM productivities, a tuyere coke sampler was used to collect the coke samples for measuring the coke strength. Firstly, the difference of sampled coke under the conditions of various HM productivities was explored. Secondly, the BF operating conditions and causes of generating more coke fines was correlated by testing the coke abrasion rate after reaction. Finally, according to the above analysis results, the relative regression equations had been obtained for sampling coke properties, BF operation conditions and BF permeability. Furthermore, the coke strength after reaction (CSR) quantitative target and its online system at various blast conditions were set to provide some reference for coke and HM production.